A Novel Technique for Donor Insertion and Unfolding in Descemet Membrane Endothelial Keratoplasty. Issue 8 (August 2021) - Fogla, Rajesh; Thazethaeveetil, Indumathy Ramachandran
Abstract : Purpose: To describe a novel technique for insertion and unfolding of donor Descemet membrane (DM) scroll during DM endothelial keratoplasty (DMEK). Methods: DMEK was performed in 20 eyes. The donor DM scroll was loaded into a glass injector, and the fluid column was manipulated to achieve a double scroll configuration. After performing DM stripping and inferior iridectomy, an anterior chamber (AC) maintainer was placed in position. The glass injector was inserted into the AC and the tip rotated to ensure correct orientation of the DM scroll. After disconnecting the IV tubing from the AC maintainer, the donor DM scroll was delivered into the AC. Donor unfolding was performed using surface tapping techniques. An air bubble was injected under the graft to obtain a complete AC air fill. The outcomes of this surgical technique were analyzed. Results: Donor DM insertion and unfolding were performed without any complications in all eyes. Double scroll configuration of donor DM in the injector could be achieved in 17 of 20 eyes (85%). A controlled delivery, maintaining correct scroll orientation, was possible in all eyes. Intraoperative duration from insertion to unfolding was 252.7 ± 45.4 seconds. A clear cornea was achieved in all eyes, with 75% of eyes (15/20) achieving corrected distance visual acuity of 20/20 or better, at average follow-up duration of 13.3 ± 1.3 months. Endothelial cell loss at 6 months follow-up was noted to be 16.7%. Partial donor detachment was noted in 2 eyes (10%), which resolved spontaneously. Conclusions: Our novel technique of donor DM insertion allows easy donor insertion and unfolding, thereby simplifying the DMEK procedure. Abstract : Supplemental Digital Content is Available in the Text.